Unusual Presentation of Pseudoaneurysm with Trochanteric Fracture Femur with Associated Long-Term Antiepileptic Therapy. (12th August 2014) - Rana, Nipun; Dhaked, Gajanand; Sharma, Satish; Tripathi, Sandeep
Abstract : Arterial injury following impalement due to a trochanteric hip fracture-fragment per se has been documented rarely. We report a case of pseudoaneurysm of profunda femoris artery at the first perforator branch in a 48-year-old male, with trochanteric hip fracture following a fall during an epileptic episode. Persistent recalcitrant pain, globular swelling in the groin, unexplained drop in the haemoglobin level, and color doppler ultrasonography findings were salient features to the diagnosis. Additionally, we collected all reported cases of pseudoaneurysm associated with hip fractures. We reviewed the literature regarding the incidence, treatment, and prognosis for the same. Acute vascular injury was probably caused by the spikes of fractured lesser trochanter which was found to be displaced superomedially. All trochanteric fractures especially those with displaced lesser trochanter fragment should be closely watched for the possibility of vascular injury. Early diagnosis and treatment in a staged manner can prevent the catastrophic vascular event and hence the limb.